2020
DOI: 10.1101/2020.01.08.898635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin B12is neuroprotective in experimental pneumococcal meningitis through modulation of hippocampal DNA methylation

Abstract: AbstractBackgroundBacterial meningitis (BM) causes apoptotic damage to the hippocampus and homocysteine (Hcy) accumulation to neurotoxic levels in the cerebrospinal fluid of children. The Hcy pathway controls bioavailability of methyl and its homeostasis can be modulated by vitamin B12, cofactor of the methionine synthase enzyme. Herein, the neuroprotective potential and the underlying mode of action of vitamin B Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…While the precise mechanisms by which VB12 deficiency induces neuropsychiatric conditions remains unclear, several vital functions of VB12 are likely to be relevant. VB12 protects against oxidative injury and inflammatory stress by directly scavenging free radical species and suppressing oxidation-induced injury, supporting glutathione activity, reducing endoplasmic reticulum stress and resisting neuronal apoptosis in several models of neurological disease [10].…”
Section: Neurologic Complications Of Vitamin B12 Deficiencymentioning
confidence: 99%
“…While the precise mechanisms by which VB12 deficiency induces neuropsychiatric conditions remains unclear, several vital functions of VB12 are likely to be relevant. VB12 protects against oxidative injury and inflammatory stress by directly scavenging free radical species and suppressing oxidation-induced injury, supporting glutathione activity, reducing endoplasmic reticulum stress and resisting neuronal apoptosis in several models of neurological disease [10].…”
Section: Neurologic Complications Of Vitamin B12 Deficiencymentioning
confidence: 99%
“…B12 supplementation has also been shown to promote DNA methylation changes and affect the antidepressant response in a mouse model [ 161 ]. Supplementation also restores hippocampal DNA methylation levels in rats with bacterial meningitis [ 162 ]. These studies suggest that B12 supplementation could be explored in scenarios where increased methylation potential is required, analogous to the FA supplementation of pregnant women to prevent NTDs.…”
Section: Targeting One-carbon Metabolism For the Treatment Of Disementioning
confidence: 99%
“…Besides, as a therapeutic drug of Alzheimer's disease‐related cognitive disorder, MeCbl treatment significantly decreased homocysteine level in blood, which was an indicator of neuroinflammation 68 . Coimbra and colleagues suggested that the repressive effect of MeCbl on neuroinflammtion was partly through modulation of DNA methylation of certain inflammatory cytokines 69 . However, the underlying mechanism for the anti‐inflammatory effect of MeCbl on AIPN is warranted for further research.…”
Section: Discussionmentioning
confidence: 99%
“…68 Coimbra and colleagues suggested that the repressive effect of MeCbl on neuroinflammtion was partly through modulation of DNA methylation of certain inflammatory cytokines. 69 However, the underlying mechanism for the anti-inflammatory effect of MeCbl on AIPN is warranted for further research.…”
Section: As-induced Mechanical Hyperalgesia and Neuroinflammation Imentioning
confidence: 99%